PENGEMBANGAN INTERVENSI PROMOSI KESEHATAN UNTUK MENINGKATKAN KESIAPSIAGAAN BENCANA KEBAKARAN DI SEKOLAH MENENGAH - Tuti Surtimanah; Gugum Pamungkas; Siti Salma Alfiyanti; Safa Qurani Fatiha; Denok Salindri; Dani Murdaya; Ratu Ayya (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2026)
Introduction: The high incidence of fire disasters in Bandung—198 cases in 2017, averaging 16.5 incidents per month and affecting an area of 3,316 m²—underscores the urgent need for promotive interventions in fire prevention and preparedness, particularly in school settings. Schools, as densely populated and high-risk environments, require health promotion-based approaches to enhance awareness and emergency response capacity among students. This study aimed to assess students' knowledge of fire disaster preparedness at SMK Negeri 8 Bandung and to develop a health promotion intervention. The intervention included the establishment of a school disaster preparedness team, fire response training, development of infographic-based educational media, and hands-on practice using fire extinguishers (APAR). Methode: A mixed-method approach with a Research and Development (R&D) design was employed. Results showed that students' knowledge was initially low. Results: Post-intervention, there was a significant increase in knowledge (Wilcoxon test, p = 0.002). Students demonstrated the ability to correctly and safely operate fire extinguishers. A formal disaster preparedness team was established through a school decree and is currently implementing an action plan. The educational media received highly positive evaluations (average score: 97.8). Conclusion: These findings indicate that comprehensive health promotion interventions can significantly improve school fire preparedness. Continued support for training, educational materials, and preparedness infrastructure is essential as part of sustainable promotive and preventive strategies in educational institutions.